Gastrojejunal Stoma Diameter Predicts Weight Regain after Roux-en-Y Gastric Bypass - Abu Dayyeh, Barham K. (2010)
BACKGROUND & AIMS: Weight regain following Roux-en-Y gastric bypass (RYGB) is associated with reductions in health status and quality of life. We evaluated whether gastro-jejunal stoma diameter is a risk factor for weight regain after RYGB. METHODS: We examined data collected over 4 years from consecutive patients referred to a tertiary care bariatric center for upper endoscopy after RYGB. We used linear regression analysis to determine the association between the gastro-jejunal stoma diameter and weight regain. We applied a logistic regression model using clinical and endoscopic parameters to develop a prediction rule for weight gain after RYGB. RESULTS: Among 165 patients included in our study, 59% had significant weight regain (≥ 20% of maximum weight lost after the RYGB) and 41% did not. The mean percent of maximal weight lost after RYGB that was regained in the entire cohort was 30% ± 22%. Gastro-jejunal stoma diameter was significantly associated with weight regain after RYGB surgery in univariate analysis (β = 0.31, P < 0.0001). This association remained significant after adjusting for several known or purported risk factors for weight regain (β = 0.19, P=0.003). We developed a simple prediction rule for weight regain after RYGB using a 7 point scoring system that includes the gastro-jejunal stoma diameter, race, and percent maximal body weight lost after RYGB; a cut-off score ≥ 4 points had an area under receiver operating characteristic curve of 0.76 and a positive predictive value of 75%. CONCLUSION: Increased gastro-jejunal stoma diameter is a risk factor for weight regain after RYGB and can be incorporated in a novel prediction rule.